2011
DOI: 10.1007/s10753-011-9318-4
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Pretreatment Attenuates Lung and Kidney Injury in Cholestatic Rats Induced by Hepatic Ischemia/Reperfusion

Abstract: Hepatic ischemia followed by reperfusion (IR) results in mild to severe organ injury, in which tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) seem to be involved. Thus, we aim to assess the influence of hepatic ischemia/reperfusion injury on remote organs in addition to cholestasis and consider the possible efficacy of steroid pretreatment in reducing the injury. A common bile duct ligation model was done on 24 male Sprague-Dawley rats. After 7 days, the rats were divided randomly into control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…As a kind of glucocorticoids, dexamethasone was widely used in the clinical studies for the treatment of kidney injury [36][39]. In succession, its therapeutic function for different kidney injury animal models (cyclosporine A nephrotoxicity injury, ischemia/reperfusion injury, uranyl nitrate induced injury, endotoxin induced injury and gentamicin nephrotoxic injury) has been demonstrated, and associated mechanisms, such as ameliorating microvascular oxygenation and stabilizing TRPC6 expression and distribution, were also investigated by several groups [34], [40][45]. Therefore, it was chosen as the positive drug in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of glucocorticoids, dexamethasone was widely used in the clinical studies for the treatment of kidney injury [36][39]. In succession, its therapeutic function for different kidney injury animal models (cyclosporine A nephrotoxicity injury, ischemia/reperfusion injury, uranyl nitrate induced injury, endotoxin induced injury and gentamicin nephrotoxic injury) has been demonstrated, and associated mechanisms, such as ameliorating microvascular oxygenation and stabilizing TRPC6 expression and distribution, were also investigated by several groups [34], [40][45]. Therefore, it was chosen as the positive drug in our study.…”
Section: Discussionmentioning
confidence: 99%
“…29 Briefly, kidney samples were homogenized separately in 0.1  M NaCl, 0.05  M Tris-Cl and 2% (v v −1 ) Triton X-100 together with protease inhibitors (Roche Diagnostics, Melbourne, Australia). After centrifugation, the supernatants were collected and stored at −80 °C until assayed.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers (Gedik et al, 2012;Li et al, 2012;Wang et al, 2012) have found that lung inflammatory injury and acute myocardial damage caused by I/R injury is related to the production of TNF-α after reperfusion. In a recent study, Zhou et al (2012) found that the expression of TNF-α and IL-1β in lung and kidney tissue was significantly increased after hepatic I/R. It was believed that there was progressive impairment of cognitive function in patients 2 to 7 days after surgery, peaking on the 4th or 5th day (Kilo et al, 2001), and it was considered that a different degree of surgical invasion had a different influence on the cognitive function of surgical patients (Müller et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…The common causes for POCD were anesthesia and surgical trauma, especially cardiac surgery and neurosurgery, which usually lead to the ischemia/ reperfusion (I/R) injury. Hepatic surgery, which also can cause I/R injury, although causing distant organ injury such as to lung, intestine and kidney (Colletti and Green, 2006;Jildenstal et al, 2011;Kadkhodaee et al, 2012;Zhou et al, 2012), has not been studied much in that regard.…”
Section: Introductionmentioning
confidence: 99%